2005
DOI: 10.1111/j.1572-0241.2005.40966.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinical Characteristics between Patients with Endoscopy-Negative Reflux Disease and Erosive Esophagitis in Japan

Abstract: Female gender, low BMI, not smoking, absence of hiatal hernia, and severity of gastric atrophy were positively associated with endoscopy-negative reflux disease compared with erosive esophagitis among Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 36 publications
10
80
3
1
Order By: Relevance
“…Smoking was inversely related to NERD compared with RE [22] . Smoking decreases lower esophageal sphincter pressure and increases the frequency of reflux episodes.…”
Section: ) Patientsmentioning
confidence: 97%
See 2 more Smart Citations
“…Smoking was inversely related to NERD compared with RE [22] . Smoking decreases lower esophageal sphincter pressure and increases the frequency of reflux episodes.…”
Section: ) Patientsmentioning
confidence: 97%
“…The previous studies showed that male gender is a risk factor for erosive esophagitis; whereas female is more likely to be associated with NERD [21,22] . Less parietal cell mass in women may be underlining reasons for the lower risk of GE [23] .…”
Section: ) Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first prospective population-based study to explore an association between chronic HBV infection and GERD. The increased incidence of GERD in HBV carriers was independent of other known risk factors [16][17][18]. Moreover, we found a differential association between genders and APRI levels, and chronic HBV infection was an independent risk factor of erosive esophagitis, especially in female subjects and Data are shown by mean ± standard deviation or proportion of the character P \ 0.05 is considered as statistical significance those with higher APRI levels.…”
Section: Discussionmentioning
confidence: 75%
“…14,17,22,2 Furthermore, there is a stronger negative association between H. pylori infection and endoscopically-demonstrated reflux oesophagitis than between H. pylori and GORD without macroscopic oesophagitis. [26][27][28] …”
Section: H Pylori and Gord Complications In East Asiamentioning
confidence: 99%